The price of possessiveness: how parental materialism undermines child psychological wellbeing - Miao Li (Frontiers in Child and Adolescent Psychiatry)
Materialism, a value system that places the pursuit of possessions at the core of happiness and life meaning, is a dominant cultural force in modern societies. While its associations with individual well-being are well-documented, its intergenerational implications remain understudied. This study conceptualizes materialism as a potential family stressor contributing to the intergenerational transmission of stress. An intergenerational crossover model of materialism was tested using data from 1,996 parent-child pairs in Zhengzhou, China. Results indicate that higher parental materialism is associated with stronger materialistic values in children, weaker family relationships, and more frequent parental comparisons, each of which is linked to greater psychological distress in youth. These patterns suggest that materialism may contribute to intergenerational patterns of vulnerability. The study highlights the cultural dimensions of mental health and provides a theoretical tool for further research on how materialism, as modernity's “default value”, relates to health inequalities.